1991
DOI: 10.1073/pnas.88.10.4162
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic regulation of bradykinin-induced plasma extravasation and adjuvant-induced arthritis in the rat.

Abstract: We assessed the contribution of ATP and adenosine (i) to a major sign of acute inflammation, plasma extravasation (PE), in the rat knee joint and (ii) to the severity of joint injury in adjuvant-induced experimental arthritis, a chronic inflammatory disease. PE induced by local infusion of bradykinin, which we have previously shown to depend on the sympathetic postganglionic neuron terminal, was markedly enhanced by coinfusion of either ATP or the adenosine A2-receptor agonist 2-[4-(2-carboxyethyl)phenylethyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 28 publications
3
47
0
Order By: Relevance
“…The selective A 1 receptor antagonist 8-cyclopentyl-1,3-dipropylxanthine (DPCPX), A 2 antagonist 3,7-dimethyl-1-propargylxanthine (DMPX), 3-isobutyl-1-methylxanthine, protein kinase inhibitor (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24), dipyridamole, and S-(4-nitrobenzyl)-6-thioinosine (NBTI) were obtained from Research Biochemicals (Natick, MA). RPMI 1640, FCS, and penicillin-streptomycin were obtained from Life Technologies (Grand Island, NY).…”
Section: Micementioning
confidence: 99%
See 1 more Smart Citation
“…The selective A 1 receptor antagonist 8-cyclopentyl-1,3-dipropylxanthine (DPCPX), A 2 antagonist 3,7-dimethyl-1-propargylxanthine (DMPX), 3-isobutyl-1-methylxanthine, protein kinase inhibitor (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24), dipyridamole, and S-(4-nitrobenzyl)-6-thioinosine (NBTI) were obtained from Research Biochemicals (Natick, MA). RPMI 1640, FCS, and penicillin-streptomycin were obtained from Life Technologies (Grand Island, NY).…”
Section: Micementioning
confidence: 99%
“…The nucleoside adenosine is the best characterized of these purines, as both extracellular and intracellular adenosine have been shown to affect almost all aspects of an immune response (1)(2)(3). Adenosine and its analogues can alter the course of a variety of immunemediated/inflammatory diseases such as endotoxin shock (4,5), rheumatoid arthritis (6,7), pleural inflammation (8), nephritis (9), or uveitis (10). Adenosine is also recognized as one of the most important endogenous molecules able to prevent tissue injury in ischemia-reperfusion (11).…”
mentioning
confidence: 99%
“…In lymphocytes, adenosine inhibits the synthesis of immunoglobulins (Moroz & Stevens, 1980) and lymphocyte-mediated cytolysis (Wolberg et al, 1975). Recent in vivo studies have demonstrated a protective role of adenosine and its structural analogues in models of acute inflammation such as experimental adjuvant arthritis (Green et al, 1991), ischaemia-reperfusion (Grisham et al, 1989;Kaminski & Proctor, 1989;Forman et al, 1993;Marts et al, 1993) and carregeenin-induced pleural inflammation (Schrier et al, 1990). Furthermore, methotrexate, an antifolate commonly used in the treatment of rheumatoid arthritis patients, causes accumulation of adenosine and inhibition of leukocyte migration in inflammatory exudates in mice (Cronstein et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Adenosine is an endogeneous immunomodulator with anti-inflammatory properties (Daval et al, 1991(Daval et al, , 1996Cronstein, 1994). This purine nucleoside ameliorates the fate of a variety of immune-mediated diseases such as pleural inflammation (Schrier et al, 1990), ischemia-reperfusion injury (Janier et al, 1993;Bouma et al, 1997), brain ischemia and trauma (Marangos et al, 1990), rheumatoid arthritis (RA) (Green et al, 1991;Szabo et al, 1998), and endotoxin-mediated shock (Parmely et al, 1993;Hasko et al, 1996). Several of these effects could be explained by the ability of adenosine to suppress TNF produced by activated macrophages and Kupffer cells (Bouma et al, 1994;Reinstein et al, 1994;McWhinney et al, 1996;Bowlin et al, 1997;Hasko et al, 2000a) and to suppress expression of adhesion molecules by activated human endothelial cells (Bouma et al, 1996).…”
Section: Introductionmentioning
confidence: 99%